MEETING OF MUSEOLOGY SPECIALISTS IN THE ANCIENT LAND OF UZBEKISTAN - E.I. Kubasheva (Research Retrieval and Academic Letters, 2024)
This article talks about educational trips aimed at improving the skills of Kazakh museum workers using the example of trips to Uzbekistan and France. The world society undergoing global changes also requires the comprehensive development of specialists in the field of culture and art, and the application of skills in their work. Modern technological methods and techniques provide opportunities for profitable organization, conduct of museum work, and increasing the interest of visitors through their participation in cultural processes. Solutions to these questions are presented from a comparative, educational point of view